Mito‐Bomb: Targeting Mitochondria for Cancer Therapy - Guo, Xiaolu; Yang, Naidi; Ji, Wenhui; Zhang, Hang; Dong, Xiao; Zhou, Zhiqiang; Li, Lin; Shen, Han‐Ming; Yao, Shao Q.; Huang, Wei (Advanced materials (Weinheim), 2021)
Cancer has been one of the most common life‐threatening diseases for a long time. Traditional cancer therapies such as surgery, chemotherapy (CT), and radiotherapy (RT) have limited effects due to drug resistance, unsatisfactory treatment efficiency, and side effects. In recent years, photodynamic therapy (PDT), photothermal therapy (PTT), and chemodynamic therapy (CDT) have been utilized for cancer treatment owing to their high selectivity, minor resistance, and minimal toxicity. Accumulating evidence has demonstrated that selective delivery of drugs to specific subcellular organelles can significantly enhance the efficiency of cancer therapy. Mitochondria‐targeting therapeutic strategies are promising for cancer therapy, which is attributed to the essential role of mitochondria in the regulation of cancer cell apoptosis, metabolism, and more vulnerable to hyperthermia and oxidative damage. Herein, the rational design, functionalization, and applications of diverse mitochondria‐targeting units, involving organic phosphine/sulfur salts, quaternary ammonium (QA) salts, peptides, transition‐metal complexes, guanidinium or bisguanidinium, as well as mitochondria‐targeting cancer therapies including PDT, PTT, CDT, and others are summarized. This review aims to furnish researchers with deep insights and hints in the design and applications of novel mitochondria‐targeting agents for cancer therapy. The concept of “Mito‐Bomb Tumor Therapy” is proposed from an interdisciplinary perspective of “biology–chemistry–materials,” and the biological functions of mitochondria, mitochondria‐targeting functional units, and various cancer treatment strategies that target mitochondria, including but not limited to photothermal therapy, photodynamic therapy, and chemodynamic therapy are summarized in detail.